275 Translational endpoints associated with STK11 mutations in patients with non-squamous NSCLC. (9th November 2020) - Wu, Song; Standifer, Nathan; Reyes, Melissa de los; Oberst, Micheal; Raja, Rajv; Barrett, Carl; Ascierto, Maria
Abstract : Background: Emerging data suggest poor outcome to anti- PD(L)1 blocking agents in patients with STK11mut tumors1. In the current study, we undertook in-depth translational evaluations of three Ph1/Ph2 independent studies of Durvalumab ± Tremelimumab to elucidate the biology associated with STK11 mutations leading to reduced clinical response in patients with non-squamous NSCLC. Methods: Mutational status was evaluated by ctDNA or Foundation One CDx as previously described1. RNA sequencing was conducted on baseline frozen biopsies (N=70). Selected proteins (N=66) were measured by Myriad RBM multiplexed immunoassays on baseline serum (n=91). Screening and longitudinal whole blood was assessed for circulating quantities of T, B or NK cells and activated or memory T cell subsets using bioanalytically-validated, flow cytometry-based immunophenotyping assays. Exploratory analyses of translational endpoints according to STK11 mutational status were conducted by Wilcoxon rank-sum test. Results: In the periphery, a reduced number (> 2-fold decreased in median quantities) of NK cells, CD4+ effector memory, CD4+ HLA-DR+, CD8+ effector memory and CD8+ HLA-DR+ T cells was observed at baseline and following treatments in patients with STK11mut vs. STK11wt tumors. At baseline, increased levels of IL6 (p=0.002) and the neutrophil-attracting cytokine IL8 (p=0.02) were found in serum of patients with STK11mut tumors. In the tumor microenvironment, significantly increased expression (p< 0.05; fold change > 2) of markers associated with neutrophils, (i.e. CXCL2, IL6, CSF3), Th17 contexture (i.e. IL17A) and immune checkpoints (i.e. KIRs, PD-L1) was found in STK11mut vs. STK11wt tumors. Conclusions: The poor outcomes to immunotherapy observed in NSCLC patients with STK11mut tumors might be determined by a compromised peripheral and intra-tumoral immune phenotype. These results might help the development of novel therapeutic interventions able to unleash response to immune checkpoints in NSCLC patients harboring STK11 mutations. Trial Registration: NCT01693562, NCT02087423, NCT02000947 Reference: Jure Kunkel Met al, JCO. 2018.36.15_suppl.3028.